Literature Review terhadap Kepuasan Kerja: Pengaruh Komunikasi dan Lingkungan Kerja - Hanna Luthfiana; Muhammad Richo Rianto (Penerbit Goodwood, 2023)
Purpose: The purpose of this paper is to determine whether there is a significant influence between communication and the work environment on job satisfaction. Research Methodology: The study uses “Literature Review” which use Google Scholar to collect data from online journal article literature. Result: The result of this writing is that communication and work environment affect job satisfaction. Limitation: This research was only conducted on employees in a company, these variables include communication, work environment and job satisfaction. Contribution: This research is expected to be useful for companies in realizing effective communication and a good work environment, so that there is an increase in job satisfaction for employees.